Epidemiology and clinical presentation of gonorrhoea in England and Wales: findings from the Gonococcal Resistance to Antimicrobials Surveillance Programme 2001–2006. Issue 5 (20th April 2009) - Delpech, V; Martin, I M C; Hughes, G; Nichols, T; James, L; Ison, C A; ,
Abstract : Objective: To analyse the enhanced data for gonorrhoea cases in England and Wales collected by the Gonococcal Resistance to Antimicrobials Surveillance Programme (GRASP) to better inform health policy and targeted interventions. Methods: GRASP data obtained annually from sentinel genitourinary medicine (GUM) clinics between June to August during 2001–6 were analysed. Results: A total of 12 282 cases of gonorrhoea were reported during the study period, with a decline over time primarily in heterosexual patients of black ethnicity. 73% of women, 47% of heterosexual men and 22% of men who have sex with men (MSM) were aged under 25. Most infected women reported a single sexual partner in the previous 3 months, whereas most heterosexual men and MSM reported two or more partners. A history of gonorrhoea was reported by 42% of MSM, 30% of heterosexual men and 20% of women. Excluding HIV, women were more likely than men to have a concurrent STI at diagnosis, most commonly chlamydia (50% vs 27% p<0.0005). Rectal gonococcal infections were reported in 35% and HIV co-infection in 31% of MSM. Compared to HIV negative MSM, those co-infected with HIV were older (median 35 years vs 28 years) and were more likely to attend a London site (70% vs 52%, p<0.0005); have a concurrent sexually transmitted infection (STI) (28% vs 20%, p = 0.002); have a history of gonorrhoea (66% vs 36%, p<0.0005) and have more sexual partners (average 6.8 vs 4.3). Conclusion: Gonorrhoea is concentrated within specific groups who are at high risk of repeat infections and concurrent STIs including HIV. Targeted interventions of proved effectiveness are urgently required.